Home Environment and Learning Interest as Predictors of Social Studies Achievement Among Sixth-Grade Elementary Students: A Correlational Study in the Digital Era - Dina Angraini; Weni Yulastri; Alfroki Martha (Journal of Education Research, 2026)
The quality of students' academic performance is shaped by a complex interplay of familial and motivational factors. This study aimed to analyze the effects of the family environment and learning interest on Social Studies learning outcomes among sixth-grade students at public elementary schools in Gunung Raya District. A quantitative ex post facto design was employed, with all 85 sixth-grade students from five schools serving as research subjects through a total sampling technique. Data were collected through a four-point Likert scale questionnaire and end-of-semester grade documentation, and analyzed using multiple linear regression. The findings revealed that both the family environment and learning interest had significant positive effects on students' Social Studies learning outcomes, either partially or simultaneously, with both variables jointly accounting for 50.0% of outcome variance (R² = .50; F = 62.34; p < .001). The family environment emerged as the stronger predictor (β = .48) compared to learning interest (β = .32). These results underscore the critical role of a supportive home environment and intrinsic motivation in enhancing elementary students' academic achievement in Social Studies.